Age of first exposure to soccer heading and sensory reweighting for upright stance - Caccese, J. B.; Santos, F. V.; Yamaguchi, F.; Jeka, J. J. (International Journal of Sports Medicine, 2020)
US Soccer eliminated soccer heading for youth players ages 10 years and younger and limited soccer heading for children ages 11-13 years. Limited empirical evidence associates soccer heading during early adolescence with medium-to-long-term behavioral deficits. The purpose of this study was to compare sensory reweighting for upright stance between college-aged soccer players who began soccer heading ages 10 years and younger (AFE = 10) and those who began soccer heading after age 10 (AFE > 10). Thirty soccer players self-reported age of first exposure (AFE) to soccer heading. Sensory reweighting was compared between AFE = 10 and AFE > 10. To evaluate sensory reweighting, we simultaneously perturbed upright stance with visual, vestibular, and proprioceptive stimulation. The visual stimulus was presented at two different amplitudes to measure the change in gain to vision, an intra-modal effect; and change in gain to galvanic vestibular stimulus (GVS) and vibration, both inter-modal effects. There were no differences in gain to vision (p=0.857, Eta2=0.001), GVS (p=0.971, Eta2=0.000), or vibration (p=0.974, Eta2=0.000) between groups. There were no differences in sensory reweighting for upright stance between AFE = 10 and AFE > 10, suggesting that soccer heading during early adolescence is not associated with balance deficits in college-aged soccer players, notwithstanding potential deficits in other markers of neurological function.